Biofilm-dispersed pneumococci induce elevated leukocyte and platelet activation - Chao, Yashuan; Mørch, Martina; Håkansson, Anders P.; Shannon, Oonagh (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionStreptococcus pneumoniae (the pneumococcus) effectively colonizes the human nasopharynx, but can migrate to other host sites, causing infections such as pneumonia and sepsis. Previous studies indicate that pneumococci grown as biofilms have phenotypes of bacteria associated with colonization whereas bacteria released from biofilms in response to changes in the local environment (i.e., dispersed bacteria) represent populations with phenotypes associated with disease. How these niche-adapted populations interact with immune cells upon reaching the vascular compartment has not previously been studied. Here, we investigated neutrophil, monocyte, and platelet activation using ex vivo stimulation of whole blood and platelet-rich plasma with pneumococcal populations representing distinct stages of the infectious process (biofilm bacteria and dispersed bacteria) as well as conventional broth-grown culture (planktonic bacteria).MethodsFlow cytometry and ELISA were used to assess surface and soluble activation markers for neutrophil and monocyte activation, platelet-neutrophil complex and platelet-monocyte complex formation, and platelet activation and responsiveness.ResultsOverall, we found that biofilm-derived bacteria (biofilm bacteria and dispersed bacteria) induced significant activation of neutrophils, monocytes, and platelets. In contrast, little to no activation was induced by planktonic bacteria. Platelets remained functional after stimulation with bacterial populations and the degree of responsiveness was inversely related to initial activation. Bacterial association with immune cells followed a similar pattern as activation.DiscussionDifferences in activation of and association with immune cells by biofilm-derived populations could be an important consideration for other pathogens that have a biofilm state. Gaining insight into how these bacterial populations interact with the host immune response may reveal immunomodulatory targets to interfere with disease development.